1979
DOI: 10.1093/cvr/13.12.703
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of shortening of the normal human left ventricle

Abstract: Left ventricular sequence of shortening was studied through the analysis of cineventriculograms in 30 degree right anterior oblique projection of 11 normal patients. In all patients transverse shortening progressed in base to apex direction, in a concentric fashion. Base descent started simultaneously with the first transverse inward motion and continued throughout systole. There was a slight protrusion of the apex in the beginning of systole, lasting a mean of 115 ms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…But additional mechanisms should be operative since it has been shown that in the pre-ejection period there is already a movement of the base towards the apex and a protrusion of the apex [18,; this seems, in essence, a movement of translation of the left ventricle and the protrusion of the apex should represent the apical impulse, that also begins in the pre-ejection period [33]. As it was shown that in the pre-ejection period there is a decrease in volume of the left ventricle [34] owing to transference of blood to the left atrium by movement of the mitral leaflets in posterior direction, we raised the hypothesis that this could also produce a recoil of the left ventricle [21]. Studies of the sequence of contraction (shortening) of the human left ventricle [21, have shown that the apex is the latest segment to contract and the base is among the earliest [21,.…”
Section: Physiological Aspectsmentioning
confidence: 96%
See 1 more Smart Citation
“…But additional mechanisms should be operative since it has been shown that in the pre-ejection period there is already a movement of the base towards the apex and a protrusion of the apex [18,; this seems, in essence, a movement of translation of the left ventricle and the protrusion of the apex should represent the apical impulse, that also begins in the pre-ejection period [33]. As it was shown that in the pre-ejection period there is a decrease in volume of the left ventricle [34] owing to transference of blood to the left atrium by movement of the mitral leaflets in posterior direction, we raised the hypothesis that this could also produce a recoil of the left ventricle [21]. Studies of the sequence of contraction (shortening) of the human left ventricle [21, have shown that the apex is the latest segment to contract and the base is among the earliest [21,.…”
Section: Physiological Aspectsmentioning
confidence: 96%
“…As it was shown that in the pre-ejection period there is a decrease in volume of the left ventricle [34] owing to transference of blood to the left atrium by movement of the mitral leaflets in posterior direction, we raised the hypothesis that this could also produce a recoil of the left ventricle [21]. Studies of the sequence of contraction (shortening) of the human left ventricle [21, have shown that the apex is the latest segment to contract and the base is among the earliest [21,. If so, translational movement of the left ventricle would go unopposed by movement of the apex in the pre-ejection period, thus leading to protrusion of that region and the apical impulse.…”
Section: Physiological Aspectsmentioning
confidence: 99%